Enid blyton's claudine at st clare's - Blyton, Enid (Mammoth London, 1996)
St. Clare's boarding-school has some interesting newcomers. Claudine, a French girl, causes great excitement by doing and saying exactly what she likes, and Eileen's mother is the new Matron.